PEMANFAATAN LAHAN PEKARANGAN UNTUK BUDIDAYA AYAM KAMPUNG DENGAN PENERAPAN METODE INTENSIF - I Wayan Januartha; I Gede Arse Dana Putra I Gede Arse Dana Putra; I Gede Arse Dana Putra; Johanul Arifin Johanul Arifin (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2022)
Kampong chicken is a type of domestic chicken or not a race, many people choose to raise native chickens on a subsistence or side basis. Kampong chickens are kept in the yard of the house with a sling system or released in the yard. We chose the Kampong chickens business because the native chicken breeder has undergone many changes. Now many Kampong chickens have been developed in order to have better productivity in the future. The problem with cultivating Kampong chickens is that the land is limited in urban areas which makes people reluctant to raise/bring Kampong chickens. Then we offer a solution to the existing land limitations using intensive methods. The hope of this article can motivate people, both young and old. This business analysis uses quantitative methods by using one of the techniques, namely observation techniques that are oriented towards observation and recording by making direct and indirect observations. The purpose of using this intensive method is so that chickens are not easily infected with disease because of good cage management and farmers know how to deal with chicken disease. From the results of this business analysis, it is concluded that the "Friendly Farm" Kampong chickens farm with a scale of 218 heads and which sold 110 heads with a total sales of Rp.4.400.000,- (four million four hundred thousand) once a production period of 4 months